Komunikasi Organisasi Dalam Meningkatkan Etos Kerja Pengurus Di Himpunan Mahasiswa Islam (Hmi) Cabang Sukabumi - Dicky Andika Sulaeman; Fahrul Hafidz Hafifudin (Jurnalika : Jurnal Ilmu Komunikasi, 2023)
Organizational communication is process of communication within formal and informal organizations in a more complex form. Organizational communication consists of vertical, horizontal and diagonal communication. In an organization, giving encouragement is included as a form of motivation that is carried out to increase the work enthusiasm of the board, so that it can achieve the goals and results desired by the organization. This study uses a qualitative method with a descriptive approach. The study of organizational communication flow at the Sukabumi branch of the Himpunan Mahasiswa Islam (HMI) did not all go well. Only Horizontal and Diagonal communication flows run smoothly. Vertical communication flow (from superiors to subordinates and vice versa) is still not effective. This greatly affects the work ethic which decreases and is not optimal.